CEO dismissal: Consequences for the strategic risk taking of competitor CEOs. (15th July 2020) - Connelly, Brian L.; Li, Qiang (John); Shi, Wei; Lee, Kang‐Bok
Abstract: Research Summary: We propose that CEO dismissal can change the strategic decision‐making of CEOs at competing firms. Competitor CEOs will experience an increase in job insecurity, which motivates them to refrain from strategic risk taking. We also identify two key boundary conditions that shape the influence of CEO dismissal on competitor CEOs' risk taking. We test our ideas on a sample of CEO dismissals among S&P 1500 firms using a novel synthetic control method approach to matching. We also test the underlying theoretical mechanism using a complementary experiment on top executives. Taken together, these studies advance CEO dismissal research by investigating the spillover effect of CEO dismissal on competitor CEOs' behaviors. Managerial Summary: The position of CEO is more volatile today than ever. When it comes to pulling the trigger on CEO dismissal, companies have increasingly twitchy fingers. Therefore, it seems important to ask: when a company fires their CEO, what happens at all the other companies in the industry? We suggest the CEOs at those companies will start worrying about their job. This fear affects their strategic decision‐making. They dial back on risk and let opportunities for growth slip away. This is especially true for certain competitors. Firing a CEO, therefore, has ripple effects throughout the whole industry.